2016
DOI: 10.1017/s175173111500230x
|View full text |Cite
|
Sign up to set email alerts
|

Diet supplementation with cinnamon oil, cinnamaldehyde, or monensin does not reduce enteric methane production of dairy cows

Abstract: This study was conducted to evaluate the effect of dietary addition of cinnamon oil (CIN), cinnamaldehyde (CDH), or monensin (MON) on enteric methane (CH 4 ) emission in dairy cows. Eight multiparous lactating Holstein cows fitted with ruminal cannulas were used in a replicated 4 × 4 Latin square design (28-day periods). Cows were fed (ad libitum) a total mixed ration ((TMR); 60 : 40 forage : concentrate ratio, on a dry matter (DM) basis) not supplemented (CTL), or supplemented with CIN (50 mg/kg DM intake), C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
28
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 30 publications
8
28
2
3
Order By: Relevance
“…This results were observed especially on maize meal NDFD24, on soybean meal NDFD4 and NDFD24 and on TMR NDFD4. The cinnamaldehyde-SIL combination tended to decrease the NDFD24 compared to cinnamon oil-SIL (Benchaar 2016). In agreement with this evidence, in the present study CIN-AC-SIL had lower value of the TMR NDFD compared to the CIN-SIL at 4 h, and the differences became greater at 24 h of incubation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This results were observed especially on maize meal NDFD24, on soybean meal NDFD4 and NDFD24 and on TMR NDFD4. The cinnamaldehyde-SIL combination tended to decrease the NDFD24 compared to cinnamon oil-SIL (Benchaar 2016). In agreement with this evidence, in the present study CIN-AC-SIL had lower value of the TMR NDFD compared to the CIN-SIL at 4 h, and the differences became greater at 24 h of incubation.…”
Section: Discussionsupporting
confidence: 91%
“…Our results on TMR DMD24 apparently agree with those reported by Tager and Krause (2010), in which both eugenol and cinnamaldehyde, tested without a support, had no effect on the TMR DMD24. Similarly, in the work of Benchaar (2016), the combination cinnamon oil-SIL and cinnamaldehyde-SIL (administered at a dose of 50 mg/Kg DMI of EOAC) showed no effects on in sacco TMR DMD24. The PC EUG showed wide differences in the DMD4 results, for all the substrates, depending on the carrier used.…”
Section: Discussionmentioning
confidence: 79%
“…Eugenol is the main phenolic component of clove EO and has broad antibacterial activity against both Gram‐positive and Gram‐negative bacteria (Cobellis et al., ). It binds with HAP bacterial proteins, inactivates glycolytic enzymes and causes cell death (Benchaar, ). Several studies showed that high levels of eugenol significantly reduced ammonia (Cardozo et al., ; Patra & Yu, ; Pawar, Kamra, Agarwal, & Chaudhary, ).…”
Section: Discussionmentioning
confidence: 99%
“…Eugenol is the main phenolic component of clove EO and has broad antibacterial activity against both Gram-positive and Gram-negative bacteria (Cobellis et al, 2016). It binds with HAP bacterial proteins, inactivates glycolytic enzymes and causes cell death (Benchaar, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Os fatores que influenciam diretamente a emissão de metano entérico são a quantidade de alimento ingerido, o tipo de carboidrato na dieta, o processamento do alimento, a adição de lipídeos ou ionóforos na dieta e as alterações na microbiota ruminal, e esses fatores podem ser manipulados com o objetivo de reduzir as emissões(JOHNSON e JOHNSON, 1995). Algumas ações de mitigação, relacionadas com os fatores citados, não tiveram efeitos sobre a emissão de metano ou tiveram efeitos contrários, seja no uso de suplementos ou aditivos na dieta(BENCHAAR, 2016; GIDLUND et al, 2016), na maior digestibilidade da dieta com o uso de concentrado(SILVA et al, 2016), no nível de consumo(WARNER et al, 2017), no uso de compostos de plantas(BEAUCHEMIN et al, 2007;EBERT et al, 2017;OLIVEIRA et al, 2007).…”
unclassified